Greybody factor for an electrically charged regular-de Sitter black holes in d-dimensions - Md Sabir Ali; A. Naveena Kumara; Kartheek Hegde; C. L. Ahmed Rizwan; Shreyas Punacha; K. M. Ajith (European Physical Journal C: Particles and Fields)
Abstract We investigate the propagation of scalar fields in the gravitational background of higher-dimensional, electrically charged, regular de Sitter black holes. Using an approximate analytical approach, we derive expressions for the greybody factor for both minimally and non-minimally coupled scalar fields. In the low-energy regime, we find that the greybody factor remains non-zero for minimal coupling but vanishes for non-minimal coupling, indicating a significant influence of curvature coupling on the emission profile. Examining the greybody factor alongside the effective potential, we explore how particle parameters (the angular momentum number and the non-minimal coupling constant) and spacetime parameters (the dimension, the cosmological constant, and the non-linear charge parameter) affect particle emission. While non-minimal coupling and higher angular momentum modes generally suppress the greybody factor, the non-linear charge parameter enhances it. We then compute the Hawking radiation spectra for these black holes and observe that, despite the non-linear charge enhancing the greybody factor, both non-minimal coupling and the non-linear charge ultimately reduce the total energy emission rate. These results provide insights into how modifications to classical black hole solutions in higher dimensions, through the inclusion of non-linear electrodynamics, impact their quantum emission properties.